Aluminum‐Mediated C6‐Selective C−H Alkylation of 2‐Carbamoylbenzofuran by Nickel Catalysis. Issue 7 (8th June 2018) - Okumura, Shogo; Nakao, Yoshiaki
Abstract: Benzofuran is a key structural motif due to its bioactivity and frequent occurrence in nature. Although C−H functionalization can be one of the most efficient methods to synthesize poly‐substituted benzofurans, C6‐selective C−H functionalization has been undeveloped so far. Herein we report aluminum‐mediated C6‐selective linear alkylation of 2‐carbamoylbenzofurans with 1‐alkenes by nickel/N‐heterocyclic carbene catalysis. In the presence of a bulky aluminum additive [(2, 6‐ t Bu2 ‐4‐Me‐C6 H2 O)2 AlMe] (MAD), N, N ‐diisobutylbenzofuran‐2‐carboxamide undergoes the C6‐selective linear alkylation reaction. Different terminal alkenes can afford the corresponding C6‐alkylation products in moderate to high yields. The site‐selectivity can be understood in terms of both steric and electronic factors. Abstract : It′s just MAD ! Aluminum‐mediated C6‐selective linear alkylation of 2‐carbamoylbenzofurans with 1‐alkenes by nickel/N‐heterocyclic carbene catalysis has been reported. Bulky aluminum additive [(2, 6‐ t Bu2 ‐4‐Me‐C6 H2 O)2 AlMe] (MAD) promotes the selective alkylation reaction.